RANCANG BANGUN E-COMMERCE BERBASIS WEB PADA CV.WIJAYATAMA KOSMEDIK - Supriyanto Karya (Institut Bisnis dan Informatika Kwik Kian Gie, 2016)
Current information technology has an important role in all field and aspect of life in thebusiness world politics to economy. This is because to fulfill the public needs for information can be fulfilled with the participation of information technology. With the development of current information technology, we can perform data processing that can easily generate the information we need with accurately and minimize time and costs. This excellence is what makes current information technology many participating in all areas, one of which is a cosmetic sales efforts. On this basis, the owner of CV. Wijayatama Kosmedik want to create an e-commerce website that is used for product sales PureGlow online. E-commerce website online sales is created using the programming language PHP and HTML because this programming language is open-source and easy to use. E-commerce website consists of two sides, the front side (front end) and back side (back end). In this research, gathering information and user needs by observation, browsing, and interview with the owner of CV. Wijayatama Kosmedik. E-commerce website is designed by using object-oriented analysis and design is described by use-case diagram, sequence diagram, and entity relationship diagram. E-commerce website provides information on a wide variety of cosmetic products PureGlow, the price, and an explanation of any cosmetic product. This site also provides transaction services cosmetics PureGlow Online reservations. With the e-commerce website, the CV. Wijayatama Kosmedik can improve the quality of service in both the transaction and to provide information to customers.Key words: analysis and design, web site, e-commerce, cosmetic